1999
DOI: 10.1002/hep.510290530
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of a mouse liver organic cation transporter

Abstract: Hepatic uptake of organic cations is essential for the metabolism and secretion of numerous endobiotics and drugs. Several hepatic organic cation transporters have been kinetically defined, yet have not been isolated or cloned. We have isolated a complementary DNA (cDNA) from both murine liver and kidney cDNA libraries (mOct1/ Slc22a1), and have functionally expressed it in Xenopus laevis oocytes. Although mOct1/Slc22a1 is homologous to previously cloned rat and human organic cation transporters, organic catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
(75 reference statements)
5
34
0
Order By: Relevance
“…Several studies have shown that Oct2 plays an important role in renal secretion of creatinine in humans and mice ( 30,31 ). Additionally, methylnicotinamide, used as a model substrate for studying organic cation transport, can be regulated by Oct1 and Oct2 ( 32,33 ). In vivo, nicotinamide 1-oxide and methylnicotinamide are derived from nicotinamide.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Oct2 plays an important role in renal secretion of creatinine in humans and mice ( 30,31 ). Additionally, methylnicotinamide, used as a model substrate for studying organic cation transport, can be regulated by Oct1 and Oct2 ( 32,33 ). In vivo, nicotinamide 1-oxide and methylnicotinamide are derived from nicotinamide.…”
Section: Discussionmentioning
confidence: 99%
“…Like most members of the SLC22 family, the organic cation and carnitine transporters have a predicted membrane topology that comprises 12 a-helical transmembrane domains (TMDs), an intracellular N-terminus, a large glycosylated extracellular loop between TMDs 1 and 2, a large intracellular loop with phosphorylation sites between TMDs 6 and 7, and an intracellular C-terminus. OCT1 has been cloned from human, rat, mouse and rabbit (13)(14)(15)(16)(17), OCT2 from human (14,15), rat (18), mouse (19), rabbit (16) and pig (20) and OCT3 from human, rat and mouse (21)(22)(23). A functional active isoform of rat OCT1 (rOCT1A) missing the first TMDs and the large extracellular loop (24) and a functional active isoform of human OCT2 (hOCT2B) lacking the last three TMDs have been cloned (25).…”
Section: Cloning Of Polyspecific Organic Cation Transporters Oct Und mentioning
confidence: 99%
“…These three isoforms, cloned from rat, mouse, and man, mediate OC transport in intestine, liver, brain, and kidney. Renal expression of OCTs is species-and isoform-specific, e.g., in rat kidney, both OCT1 and OCT2 are highly expressed, whereas OCT2 is the predominant isoform in human kidney [14,15,19,29,30,32].…”
Section: Introductionmentioning
confidence: 99%